A new species of Cousinia (sect. Cousinia, Asteraceae) from the Ağrı Mountain (eastern Turkey): evidence from morphology, karyology and anatomy - Tugay, Osman; Ulukuş, Deni̇z; Ertuğrul, Kuddi̇si̇; Uysal, Tuna; Demi̇relma, Hakki; Dural, Hüseyi̇n (Phytotaxa, 2019)
Cousinia agridaghensis (sect. Cousinia) from Ağrı province, eastern Turkey, is described as new to science. The new species is morphologically closely related to C. urumiensis, C. fedorovii and C. armena but differs in capitula shape, synflorescence shape, stem height, shape of segments of basal and uppermost cauline leaves. In addition, the new species is compared with C. urumiensis, which is distributed in Turkey, in terms of chromosome number and anatomical features. The basic chromosome number is determined x = 12 in C. agridaghensis and x = 13 in C. urumiensis. The differences in leaf midrib shape and number of vascular bundles in C. agridaghensis and C. urumiensis are observed. The achene coat and pollen grain surface of C. agridaghensis and C. urumiensis are studied with SEM photographs. Furthermore, a detailed description, distribution map, conservation status and ecology of the new species are given.